Massive Gastrointestinal Bleeding From a Jejunal Dieulafoy's Lesion - Jaiswal, Palashkumar (ACG Case Rep J, 2020)
Dieulafoy's lesion is a histologically normal arteriole that has failed to progressively narrow as it navigates through the submucosa. It is a rare cause of massive gastrointestinal bleeding, occurring most often in the stomach, with only 1% of lesions occurring in the jejunum. We present the case of a 21-year-old man who presented with massive hematochezia ultimately attributed to a distal jejunal Dieulafoy's lesion, identified via an intraoperative surgically assisted deep enteroscopy. This case is unique not only regarding the unusual location of the lesion but also regarding the multidisciplinary approach necessitated for the management of this catastrophic hemorrhage that avoided surgical resection.